Giant cervico-facial mycetoma caused by Streptomyces somaliensis in a 14-year-old girl - Laouali Salissou; Saidou Mamadou; Rachid Sani; Nouhou Hassan (Our Dermatology Online, 2016)
Mycetomas are inflammatory pseudo-tumors in multiple locations that affect the skin, the subcutaneous tissues and, sometimes, the bones. Their treatment depends on the type of parasite. Fungal mycetomas, also called eumycetomas, are treated mainly through surgery, while actinomycotic mycetomas are treated primarily with drugs. We report here the case of a 14-year-old girl afflicted with a giant cervico-facial mycetoma. The patient was born to poor and illiterate parents in a rural area of the Diffa province, at 1500 km from the capital city of Niamey. Histological examination of a biopsy specimen allowed a diagnosis of actinomycetoma due to Streptomyces somaliensis. The patient showed a remarkable sensitivity to ketoconazole, but she ultimately died due to a lack of sufficient medication.